TEACHING ENGLISH IN A VIRTUAL CLASSROOM USING WHATSAPP DURING COVID-19 PANDEMIC - Rekha Asmara (Universitas Islam Ogan Komering Ilir Kayuagung, 2020)
Due to the severe situation of Covid-19 pandemic, teacher and students were forced to conduct online learning which was conducted synchronously or virtually. In a virtual classroom, teachers and students are all connected online via communication tools or their devices such as a computer, laptop, or smartphone at the same time. WhatsApp (WA) was considered as an online platform that supported the virtual classroom. Through WA, sharing information combined with some formats of file such as audio, video files, images, and location data could be done. This study was conducted to know some challenges of teaching English in a virtual classroom using WhatsApp during Covid-19 pandemic. A qualitative descriptive research method was used. The data were collected by distributing questionnaires to the fourteenstudents and an interview with the lecturer of Classroom WhatsApp group of Language in Society class.The findings displayed that the challenges were; 1) students’ attendance checking, 2) students’ English language skills, and 3) internet connection